Primary fibroblast cell cycle synchronization and effects on handmade cloned (HMC) bovine embryos - Natalia Andrea Gómez (Ciência Animal Brasileira, 2018)
Spatial and temporal synchrony and compatibility between the receptor oocyte and the donor cell nucleus are necessary for the process of embryo cloning to allow nuclear reprogramming and early embryonic development. The objective of the present study was to evaluate three cell cycle synchronization methods on a primary bovine fibroblast culture for 24, 48, or 72 h. These fibroblasts were used as nuclear donors to evaluate their in vitro developmental potential and the quality of the embryos produced through handmade cloning (HMC). No differences were found between the methods used for fibroblast synchronization in G0/G1 (p > 0.05). Production of clones from fibroblasts in four groups- no treatment at 0 h and using serum restriction SR, high culture confluence HCC, and SR+HCC at 24 h- resulted in high cleavage rates that were not different. Embryo production rates were 37.9%, 29.5%, and 30.9% in the 0h, SR24h, and SR+HHC24h groups, respectively, and 19.3% in the HCC group, which was significantly different from the other three (p < 0.05). There were no differences in the quality parameter among the clones produced with fibroblasts subjected to the different synchronization. Finally, when overall clone production was compared versus parthenotes and IVF embryos, the only difference was between clones and parthenogenetic embryos with zona pellucida (30.2% vs 38.6%). The number of blastomeres from the blastocytes produced through IVF was significantly greater than those from embryos activated parthenogenetically and from clones (117, 80, 75.9, and 67.1, respectively). The evaluation of three synchronization methods at different time points did not demonstrate an increase in the percentage of fibroblasts in the G0/G1 phases of the cell cycle; however, good quality and high cloning rates were obtained, suggesting that it is not always necessary to subject the cells to any synchronization treatments, as they would yield equally good cloning results.